Quiz and Vocab Arabic (Q&V Arabic) As Media for Mutholaah Arabic Vocabulary - Nurul Izzah; Lailatul Mauludiyah; Muhammad Ainur Roziqi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
One of the efforts to overcome the problem of Arabic language learning was to improve the understanding of vocabulary with mutholaah method. This study aimed to determine the effectiveness of muthola'ah vocabulary with Aplication Arabic Quiz and Vocab (Arabic Q&V) to improving the ability to memorize Arabic language vocabulary for grade VIII B students of islamic junior high school. The research approach used quantitative associative. The sample used 20 students. Data collection method using observation, questionnaire, and test. The data analysis techniques used are t-test related samples and N-Gain test or effectiveness test that was previously conducted prerequisite test which is normality test. The results showed a significant difference in muthola'ah The results showed that there was a significant difference from muthola'ah vocabulary before and after using Q&V Arabic application which was shown from the average pretest score of test questions 70, while the average posttest test score was 80. Muthola'ah vocabulary with Q&V Arabic application is Effectively improves the ability to memorize student